1969
DOI: 10.1139/g69-034
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Number and Duration to Floral Initiation and Flowering of Sorghum Parents and Hybrids

Abstract: Six parents and 15 hybrids of sorghum (Sorghum bicolor (L.) Moench) were grown for 3 years at Manhattan and Ashland, Kansas and observed for leaf number and time of flowering. Three parents and two hybrids were grown at Plainview, Texas for 1 year and observed for leaf number, time of floral initiation and of flowering. The data are interpreted to mean that earliness of hybrids results largely from more rapid development of the meristem prior to floral initiation and to more rapid development of the panicle in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1974
1974
1994
1994

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Breeding for early maturity usually involves selection for earliness to first flower, as appearance of the first flower and maturity are sufficiently correlated to justify its use as a selection criterion (Campbell and Kondra 1978 (Flood and Halloran 1984). This delay in floral initiation results in an increase in final leaf number (FLN) (Quinby and Liang 1969 (Salisbury et al 1979Berry et al 1980Flood and Halloran 1984;Jedel et d. 1986 (Gauss and Taylor 1969). Hodgson (1978) Further investigation revealed that the response to vernalization was cumulative and that there were differences in response among the five cultivars studied.…”
mentioning
confidence: 99%
“…Breeding for early maturity usually involves selection for earliness to first flower, as appearance of the first flower and maturity are sufficiently correlated to justify its use as a selection criterion (Campbell and Kondra 1978 (Flood and Halloran 1984). This delay in floral initiation results in an increase in final leaf number (FLN) (Quinby and Liang 1969 (Salisbury et al 1979Berry et al 1980Flood and Halloran 1984;Jedel et d. 1986 (Gauss and Taylor 1969). Hodgson (1978) Further investigation revealed that the response to vernalization was cumulative and that there were differences in response among the five cultivars studied.…”
mentioning
confidence: 99%